2009
DOI: 10.3844/jcssp.2009.33.38
|View full text |Cite
|
Sign up to set email alerts
|

Image Steganography by Mapping Pixels to Letters

Abstract: Problem statement: Steganography hides the very existence of a message so that if successful it generally attracts no suspicion at all. Using steganography, information can be hidden in carriers such as images, audio files, text files, videos and data transmissions. In this study, we proposed a new framework of an image steganography system to hide a digital text of a secret message. Approach: The main idea for this is to use enough number of bits from each pixel in an image (7-bits in this study) to map them … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(11 citation statements)
references
References 13 publications
0
11
0
Order By: Relevance
“…Before discussing the proposed method we will explain from where we got this idea, while using the internet and searching for fonts or what so called "cool fonts" that are used for chatting or presentations it has been found that new type of fonts appeared that type capital and small letters at the same time see figures (3,4,5) as an example if you typed the word "hardware" the word will be typed like this "HaRdWaRe" sometimes with different sizes for each letter and another times with same size for whole text. So, we decided to use this new font as a new text steganography method that holds bits of the secret message.…”
Section: Proposed Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Before discussing the proposed method we will explain from where we got this idea, while using the internet and searching for fonts or what so called "cool fonts" that are used for chatting or presentations it has been found that new type of fonts appeared that type capital and small letters at the same time see figures (3,4,5) as an example if you typed the word "hardware" the word will be typed like this "HaRdWaRe" sometimes with different sizes for each letter and another times with same size for whole text. So, we decided to use this new font as a new text steganography method that holds bits of the secret message.…”
Section: Proposed Methodsmentioning
confidence: 99%
“…The extracting process is traditionally a much simpler process as it is simply an inverse of the embedding process, where the secret message is revealed at the end, [11]. Cover work: used to construct a stegogramme that contains a secret message, it may be text, image, video clips or sounds, [3].…”
Section: Introductionmentioning
confidence: 99%
“…In this method the embedding should be done at high frequency coefficients. P. Mohan Kumar and D. Roopa suggested that one can apply block matching procedure to search the highest similarity block for each block of the secret image and embed in LSBs of the cover image [16]. Mohammed A.F.…”
Section: Related Work When Hiding Information Inside Images Usuamentioning
confidence: 99%
“…In contrast to Cryptography, where the enemy is allowed to detect, intercept and modify messages without being able to violate certain security premises that guaranteed by a cryptosystem. So, it can be said that the goal of Steganography is to hide messages inside other harmless messages in a way that does not allow any enemy to even detect that there is a second message present [4].…”
Section: Introductionmentioning
confidence: 99%
“…Firstly, the publishing and broadcasting industries have become interested in techniques for hiding encrypted copyright marks and serial numbers in digital films, audio recordings, books and multimedia products; an appreciation of new market opportunities created by digital distribution is coupled with a fear that digital works could be too easy to copy. Secondly, moves by various governments to restrict the availability of encryption services have motivated people to study methods by which private messages can be embedded in seemingly innocuous cover messages [4].…”
Section: Introductionmentioning
confidence: 99%